2019
DOI: 10.1097/mph.0000000000001201
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Response of Extramedullary Leukemia in Patients Treated With Gemtuzumab Ozogamicin

Abstract: Extramedullary leukemia (EML) is common in pediatric acute leukemia and can present at diagnosis or relapse. CD33 is detected on the surface of myeloid blasts in many patients with acute myelogenous leukemia and is the target of the antibody drug conjugate gemtuzumab ozogamicin (GO). Here we present 2 patients with CD33 EML treated with GO. They achieved significant response, with reduction of EML on both clinical and radiographic exams, specifically fluorine fluorodeoxyglucose positron emission tomography/com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…The response to mono-GO, or in combination with azacitidine, that has been previously described in relapsed and refractory AML patients, even with extramedullary involvement [9][10][11], the immediate response to GO in critically ill patients with pulmonary or renal failure has not been reported. Nevertheless, the mechanism of GO pharmacokinetics provides some explanation for this prompt effect.…”
Section: Discussionmentioning
confidence: 93%
“…The response to mono-GO, or in combination with azacitidine, that has been previously described in relapsed and refractory AML patients, even with extramedullary involvement [9][10][11], the immediate response to GO in critically ill patients with pulmonary or renal failure has not been reported. Nevertheless, the mechanism of GO pharmacokinetics provides some explanation for this prompt effect.…”
Section: Discussionmentioning
confidence: 93%
“…As it is the response to mono GO or in combination with Azacitidine has been previously described in R/R AML patients even with extramedullary involvements (17,18,19), although, nobody report the immediate response to Gem. Nevertheless, Mechanism of GO pharmacokinetics provides explanation for this prompt effect.…”
Section: Discussionmentioning
confidence: 97%
“…Kida et al 42 reported the results of HSCT in a patient who had extramedullary relapse myeloid sarcoma with FLT3-ITD mutation and resistance to chemotherapy; monotherapy with gilteritinib (120 mg/d) resulted in complete remission. Furthermore, cytotoxic T lymphocyte–associated protein 4 inhibitors 43 and CD33 monoclonal antibodies 44 have successfully treated myeloid sarcoma.…”
Section: Discussionmentioning
confidence: 99%